Pengaruh Nama Merek Pada Nilai Pelanggan Serta Implikasinya Terhadap Citra Daerah Dan Niat Beli - Kristi, Chikita Y.; Kurniawati, Masmira (Arthavidya Jurnal Ilmiah Ekonomi, 2019)
This paper intends to analyze the effect of brand name on customer perceived values and implications for regional images and purchase intention. Simple linear regression is applied as a technique for its data analytical. This research observed 223 respondents. The results of a positive significant relationship between customer perceived value to regional images, and customer perceived value and regional images to purchase intention. Keyword: Brand name, customer perceived values,regional images and purchase intention.